The Brand Image Of Tebing Tinggi City On Government Public Relations’ Social Media: Efforts To Maintain Its Status As The “City Of Lemang” - Putri, Ainisa; Sazali, Hasan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Tebing Tinggi City in North Sumatra has a close history with the Padang Kingdom and Datuk Bandar Kajum, which later developed into a city with a distinctive culinary identity, namely lemang. Since being introduced by the Minangkabau ethnic group in 1947, lemang has become a widely known city icon, even getting the nickname "Lemang City" since 1958. This study aims to analyze the communication strategy implemented by the Tebing Tinggi City Government Public Relations in building and maintaining the city's image through social media. With a qualitative descriptive approach, this study examines the effectiveness of digital strategies that include creating visual content, storytelling, and interacting with the community. The results of the study show that branding efforts through social media and culinary festivals have succeeded in increasing the appeal of lemang as a culinary icon and strengthening Tebing Tinggi's identity as a gastronomic tourism destination. However, challenges such as content competition and managing public perception remain the main concerns in building a sustainable city brand image.